2019
DOI: 10.4274/jtgga.galenos.2018.2018.0052
|View full text |Cite
|
Sign up to set email alerts
|

Selective fetal reduction in monochorionic twins: Preliminary experience

Abstract: Objective: In complicated mono-chorionic twin pregnancies, vaso-occlusive techniques like bipolar cord coagulation (BPCC), radiofrequency ablation (RFA), interstitial laser ablation (ILA) of cord and fetoscopy guided cord coagulation with lasers are the methods proposed for selective fetal reduction. This study brings forth preliminary data of selective fetal reduction procedures at a tertiary care center in India. Material and Methods: This was a prospective observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This rate is similar to other studies. In studies by Dadhwal et al, 8 Bebbington et al, 17 Lu et al 18 and Kumar et al, 5 the success rate was near 100%, whereas in a study by Rossi and D' Addario, failure of feticide occurred in 9% of RFA cases. 12 Paramasivam et al reported 35 cases using RFA: the technical successful rate was 100%; however, there were only three cases of TTTS Stage IV.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This rate is similar to other studies. In studies by Dadhwal et al, 8 Bebbington et al, 17 Lu et al 18 and Kumar et al, 5 the success rate was near 100%, whereas in a study by Rossi and D' Addario, failure of feticide occurred in 9% of RFA cases. 12 Paramasivam et al reported 35 cases using RFA: the technical successful rate was 100%; however, there were only three cases of TTTS Stage IV.…”
Section: Discussionmentioning
confidence: 95%
“…7 In cases with the demise of one fetus, the remaining fetus encounters some complications due to blood transfusions through placental anastomosis which results in brain hypoperfusion, brain damage (20% to 30%) and the death of the co-twin (10%). 8 Selective reduction of the fetus is one of the therapeutic methods in complicated monochorionic twins. 9 Typically, in the absence of intervention, both fetuses may die.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Ting et al 21 and Sun et al 17 also found that more than four RFA ablation cycles (adjusted odds ratio (OR), 5.21 (95% CI, 1.13-24.11)) and more than two RFA ablation cycles (adjusted OR, 3.46 (95% CI, 1.34-8.94)) were associated with a higher risk of fetal loss. A greater number of ablation cycles may be required when the procedure is hindered by conditions such as larger umbilical vessels 14,17 and suboptimal fetal or placental position 22,23 , which make it more difficult to interrupt the umbilical cord blood flow, thereby increasing the risk of thermal injury and hemodynamic deterioration 17 . However, it should be noted that there was no relationship between ablation duration and perinatal outcome in our study (Table S6) because the duration of one ablation cycle differed between individuals (Sun et al 17 reported similar findings).…”
Section: Discussionmentioning
confidence: 99%
“…10 Gaerty et al demonstrated a lower overall survival rate in both the BCO (79.1%) and RFA (76.8%) groups. 9 We added several reasonably large case series incorporating RFA, 22,23,32,33,[35][36][37]24,32,35,38 and FLC 5,28,39 patients, and included MWA and ILC in our analysis. The overall survival rates for the BCO (79.2%) and RFA (77.5%) groups in our analysis were similar to Gaerty et al, 9 but lower than in Rossi et al 10 The FLC (78.8%) and UCL (76.5%) groups showed higher overall survival rates in our analysis than in Rossi et al 10 The PPROM rate was reported as 28.2%…”
Section: Discussionmentioning
confidence: 99%